2015
DOI: 10.1101/gad.254631.114
|View full text |Cite
|
Sign up to set email alerts
|

The RNA helicase MOV10L1 binds piRNA precursors to initiate piRNA processing

Abstract: Piwi-piRNA (Piwi-interacting RNA) ribonucleoproteins (piRNPs) enforce retrotransposon silencing, a function critical for preserving the genome integrity of germ cells. The molecular functions of most of the factors that have been genetically implicated in primary piRNA biogenesis are still elusive. Here we show that MOV10L1 exhibits 5 ′ -to-3 ′ directional RNA-unwinding activity in vitro and that a point mutation that abolishes this activity causes a failure in primary piRNA biogenesis in vivo. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
207
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(220 citation statements)
references
References 77 publications
(138 reference statements)
12
207
1
Order By: Relevance
“…Mitochondriaanchored endonuclease PLD6/MITOPLD first cleaves piRNA precursor transcripts to produce the 5′ ends of piRNAs (Huang et al 2011, Watanabe et al 2011, Ipsaro et al 2012, Nishimasu et al 2012. MOV10L1, a testis-specific RNA helicase, supports the piRNA primary processing by recognizing and resolving secondary structures within the piRNA precursors (Zheng et al 2010, Vourekas et al 2015, Fu et al 2016). piRNA intermediate transcripts are then loaded on PIWI proteins that stabilize their 5′ ends.…”
Section: Germ Granules As Platforms For Pirna Pathwaymentioning
confidence: 99%
“…Mitochondriaanchored endonuclease PLD6/MITOPLD first cleaves piRNA precursor transcripts to produce the 5′ ends of piRNAs (Huang et al 2011, Watanabe et al 2011, Ipsaro et al 2012, Nishimasu et al 2012. MOV10L1, a testis-specific RNA helicase, supports the piRNA primary processing by recognizing and resolving secondary structures within the piRNA precursors (Zheng et al 2010, Vourekas et al 2015, Fu et al 2016). piRNA intermediate transcripts are then loaded on PIWI proteins that stabilize their 5′ ends.…”
Section: Germ Granules As Platforms For Pirna Pathwaymentioning
confidence: 99%
“…To test whether our 5′UTR-ORFeus transgene was regulated by the fetal piRNA pathway, we introduced the transgene into a Mov10l1-deficient genetic background (41). MOV10L1 is an RNA helicase essential for primary piRNA biogenesis (42). Global deletion of Mov10l1 leads to the loss of fetal piRNAs and malespecific meiotic defects, which are accompanied by L1 hypomethylation and up-regulation at both RNA and protein levels in postnatal Mov10l1 −/− testes (41,43).…”
Section: Developing An L1 Transgene Regulated By the Endogenous Mouse L1mentioning
confidence: 99%
“…Piwi proteins are expressed primarily in the germline, bind piRNAs and use them to target and silence transposons (Seto et al 2007;Klattenhoff and Theurkauf 2008;Ghildiyal and Zamore 2009;Senti and Brennecke 2010;Castaneda et al 2011;Siomi et al 2011;Ishizu et al 2012;Pillai and Chuma 2012;Guzzardo et al 2013;Weick and Miska 2014). CLIP-seq for Piwi proteins revealed that they may also bind directly to long RNAs without using piRNAs as guides, either in the process of piRNA biogenesis or to bind to mRNAs (Vourekas et al 2012(Vourekas et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, identifying binding sites is an important task but it also has a quite limited analysis scope. In the general case, a CLIP-seq experiment can reveal positional information for RBP sites but it can also reveal structural and mechanistic insight for the bound protein/RNA complexes (Huelga et al 2012;Vourekas et al 2012Vourekas et al , 2015Weyn-Vanhentenryck et al 2014). Moreover, RBP function might differ depending on the genomic context, and a generic CLIP-seq analysis tool has to provide a straightforward mechanism to analyze data sets under different criteria and parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation